2014
DOI: 10.1038/jp.2014.49
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on hyperglycemia and retinopathy of prematurity

Abstract: In a cohort of premature infants, elevated average blood glucose concentrations in the first week of life is independently associated with the development of ROP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 56 publications
0
42
0
Order By: Relevance
“…A few retrospective previous studies found that neonatal hyperglycaemia during the first postnatal month predicted the development of ROP 12–15 17 18. A recent prospective study by Mohsen et al 21 found a similar early association. However, possibly due to the small sample size, the study was unable to conclude on any association between neonatal hyperglycaemia and ROP treatment.…”
Section: Discussionmentioning
confidence: 68%
“…A few retrospective previous studies found that neonatal hyperglycaemia during the first postnatal month predicted the development of ROP 12–15 17 18. A recent prospective study by Mohsen et al 21 found a similar early association. However, possibly due to the small sample size, the study was unable to conclude on any association between neonatal hyperglycaemia and ROP treatment.…”
Section: Discussionmentioning
confidence: 68%
“…Hyperglycemia was significant after adjustment for the other risk factors (2,(12)(13)(14)(15) . In the literature, hyperglycemia is regarded as a marker of acute critical state, reflecting its severity and insulin resistance (1,16,17) .…”
Section: Discussionmentioning
confidence: 93%
“…Four out of 9 studies provided the mean glucose level of hyperglycemia9212225. Pooling up the data from these 4 studies showed that the mean glucose level was significantly higher in the ROP compared to the non-ROP group (SMD = 0.88, 95% CI: 0.40–1.37, I 2 = 78%, P = 0.0004, Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Seven out of the 9 studies provided primary data on the number of subjects with hyperglycemia and without hyperglycemia in both the ROP and non-ROP groups21222324252627. Pooling up data from these 7 studies showed that hyperglycemia is associated with ROP with an unadjusted OR of 4.16 (95% CI: 2.09–8.29, I 2 = 65%, P <0.0001) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation